Li effects on layer-structured oxide LixNi0.8Co0.15Al0.05O2-δ: Improving cell performance via on-line reaction. (1st February 2019) - Liu, Xueqi; Dong, Wenjing; Tong, Yuzhu; Wei, Lili; Yuan, Menghui; Wang, Xunying; Wang, Baoyuan; Zhu, Bin
Abstract: Li + plays a critically important role in layer-structured LiNiO2 family oxides in that it affects the oxidant state of Ni and catalyst's function. Layer-structured Lix Ni0.8 Co0.15 Al0.05 O2-δ (Lx NCA, x = 1, 1.2, 1.4) with different lithium content was prepared and applicated as both cathode and anode catalysts in symmetrical solid oxide fuel cell (SSOFC) that using samarium doped ceria (SDC) as electrolyte. Excess Li precursor resulted in the formation of Li2 CO3 in L1.2 NCA and L1.4 NCA materials, whose influence on the performance of Lx NCA was studied. Oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR) of Lx NCA as well as its catalytic stability were investigated by impedance spectroscopy. Its ORR process was found to be greatly influenced by the amount of Li in Lx NCA while HOR was less related to Li content. Accompanying the on-line reduction and oxidation of Lx NCA, fuel cells tested under reverse operation condition revealed enormous improvement in Pmax, which was due to the significant improvement of ORR process and the reduction of interface resistance. Highlights: Lx NCA performs good catalytic activity for both H2 and O2 . The presence of Li2 CO3 is proven to reduce interface resistance. Li + content in Lx NCA has significant effects on its ORR but not on HOR. On-line formation of Ni particle and Li2 CO3 has been observed. Study on the mechanism of improved performance in reverse operation.